Response of Application of Imperata Bokashi on the Growth and Yield of Radish on Alluvial Soil - SUARNI, ET; HADIJAH, SITI; SURACHMAN, SURACHMAN (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACTRadish (Raphanus sativus L) is a horticultural plant that is feasible to be cultivated intensively in West Kalimantan, in which a category of soil that can be used for cultivating radishes is alluvial soil. Providing of bokashi on the soil is expected to improve soil structure so that the growth of radishes can be optimized, loose soil structure will facilitate the development of radish roots. This study aims to find out one of the best dosages of bokashi for the growth and yield of radishes on alluvial soil. This research was carried out in the Experimental Garden of the Faculty of Agriculture, Tanjungpura University Pontianak, starting on 29 April 2018 to 21 June 2018 using a Completely Randomized Design (CRD) with 5 treatment levels and 5 replications. The treatment in question: K0 = without giving of imperata bokashi, K1 = 400 g/ polybag or equivalent to 10 tons/ha, K2 = 600 g/ polybag or equivalent to 15 tons/ ha, K3 = 800 g/polybag or equivalent 20 tons/ha, K4 = 1,000 g/polybag or equivalent to 25 tons/ ha. Variables observed in this study include: number of leaves, fresh weight of tubers, tuber length, tuber diameter, plant dry weight, leaf area and leaf chlorophyll. From the research that has been done, it can be concluded that the application of alang-alang bokashi dosage of 600 g/polybag was effective in increasing the number of leaves, while the effective diameter of tubers is shown in the allocation of reeds of 400g/polybag. Giving the dosage of bokashi in various dosages gave the growth of radishes that have not different significantly.                                                                                Keywords: Alluvial, Radish, Bokashi, Imperata.